2013
DOI: 10.1073/pnas.1219317110
|View full text |Cite
|
Sign up to set email alerts
|

Surface wettability plays a significant role in gecko adhesion underwater

Abstract: Although we now have thousands of studies focused on the nano-, micro-, and whole-animal mechanics of gecko adhesion on clean, dry substrates, we know relatively little about the effects of water on gecko adhesion. For many gecko species, however, rainfall frequently wets the natural surfaces they navigate. In an effort to begin closing this gap, we tested the adhesion of geckos on submerged substrates that vary in their wettability. When tested on a wet hydrophilic surface, geckos produced a significantly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
192
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(217 citation statements)
references
References 45 publications
17
192
3
Order By: Relevance
“…The mechanism behind biological adhesive systems can be complex however. Specifically, when testing geckos underwater, shear adhesion no longer relies solely on van der Waals interactions, and instead also depends on the surface energy of the substrate and its interaction with water [8]; but interestingly, not the surface chemistry of the setae [9]. Other recent studies have suggested that van der Waals forces are not the primary source of adhesion and rather are also coupled with capillary adhesion, electrostatic interactions, surface charge or even nanobubbles underwater [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism behind biological adhesive systems can be complex however. Specifically, when testing geckos underwater, shear adhesion no longer relies solely on van der Waals interactions, and instead also depends on the surface energy of the substrate and its interaction with water [8]; but interestingly, not the surface chemistry of the setae [9]. Other recent studies have suggested that van der Waals forces are not the primary source of adhesion and rather are also coupled with capillary adhesion, electrostatic interactions, surface charge or even nanobubbles underwater [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These 'non-stick' surfaces, like commercially available poly(tetrafluoroethylene) (PTFE), have been known to foil the gecko's incredible adhesive system, rendering them virtually dysfunctional (i.e. unable to support their body weight) [8,16,17]. While not many studies have investigated adhesion to wet fluorinated surfaces, the results are intriguing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 Gecko: It is not About their Feet Anymore! For over nearly a decade now, gecko's feet exhibiting remarkable adhesion properties has been a significant attraction and inspiration to many tribologists [34][35][36][37]. But this overwhelming interest toward their feet had led to ignorance of other fascinating regions of a lizard's body.…”
Section: Synovial Joint Lubrication For Ic Enginesmentioning
confidence: 99%
“…The gecko skin provides a unique topographical template for multifunctional man-made designs which may potentially aid in areas as diverse as self-cleaning of outdoor and indoor surfaces environments (e.g., hospital surfaces, habitat structures) [46][47][48] and a variety of other applications such as artificial micro-channels and circulatory channels (e.g., syringes, central line ports, next-generation animal capillaries), [49] dental implants, contact lenses, wound-healing architectures, marine structures, and membranes used in industrial applications (e.g., potable water filters) [38,[50][51][52][53][54].…”
Section: Synovial Joint Lubrication For Ic Enginesmentioning
confidence: 99%